Five years of keeping a watch on the left atrial appendage—how has the WATCHMAN fared? - Jazayeri, Mohammad-Ali (J Thorac Dis, 2016)
Left atrial appendage closure (LAAC) is a promising site-directed therapy for stroke prevention in patients with non-valvular atrial fibrillation (AF) who are ineligible or contraindicated for long-term oral anticoagulation. A variety of LAAC modalities are available, including percutaneous endocardial occluder devices such as WATCHMAN(TM) (Boston Scientific Corp., Marlborough, MA, USA), and an ever-increasing body of evidence is helping to define the optimal use of each technique. Similarly increased experience with LAAC has revealed challenges such as device-related thrombi and peri-device leaks for which the long-term significance and appropriate management are areas of active investigation. We review the evolution and long-term outcomes with the WATCHMAN(TM) device with particular emphasis on the nuances of its use and its role in the broader landscape of appendageology.